2015
DOI: 10.6018/turismo.35.221541
|View full text |Cite
|
Sign up to set email alerts
|

El uso de GPS para el análisis del comportamiento espacio-temporal de los turistas. Pre-test en el Valle de Boí

Abstract: RESUMENEste artículo es un análisis exploratorio sobre el uso de los GPS para estudiar el comportamiento de los visitantes en un espacio abierto. El Valle de Boí es un escenario turístico que ofrece diversos recursos de primer orden, por lo que el estudio de los recorridos de los visitantes permite analizar la respuesta a estímulos muy diferentes. Los resultados demuestran que el recurso del GPS en espacios abiertos permite ampliar la información sobre el uso social del espacio turístico y abre las puertas a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 38 publications
(48 reference statements)
2
9
0
5
Order By: Relevance
“…Thus, it appears that guided visitors and nonguided visitors to a heritage town do practically the same. This agrees with a study by Donaire et al (), which demonstrated that visitors to heritage places behave in a similar ritualistic way: following very specific itineraries, visiting the same attractions, and spending only a short time on the visit. It appears that sightseeing in heritage places is standard practice for tourists, whether the visit is guided or not.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, it appears that guided visitors and nonguided visitors to a heritage town do practically the same. This agrees with a study by Donaire et al (), which demonstrated that visitors to heritage places behave in a similar ritualistic way: following very specific itineraries, visiting the same attractions, and spending only a short time on the visit. It appears that sightseeing in heritage places is standard practice for tourists, whether the visit is guided or not.…”
Section: Resultssupporting
confidence: 93%
“…In addition, findings reveal that there is no significant difference in behavior between tourists on guided tours and tourists not on guided tours. The findings agree with Donaire et al (), in that visitors to heritage places behave in a similar ritualistic way, whether guided or nonguided. Both follow similar itineraries, visiting the same sights and spending a short amount of time on the visit.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Direct observation is one of the best methods for studying tourist behavior, as it provides large quantities of detailed information on the interaction between subject and object (Donaire, Galí & Royo, 2015). This means it offers real, exact information on the relationship between visitors and the place visited.…”
Section: Direct Non-participant Observation For the Study Of Tourist mentioning
confidence: 99%
“…The majority of the studies are centred on urban environments (Edwards and Griffin [6], Grinberger et al [7], Lau and McKercher [8], Shoval and Isaacson [5]) and, to a lesser extent, on natural destinations (Donaire et al [9], Hallo et al [10]), fewer studies having been conducted in coastal environments, usually associated with sun and sand tourism. Obviously, these destinations do not pose the same problems with regard to mobility as the large urban agglomerations, whilst at the same time the behaviour of the demand tends to be more passive in comparison with urban destinations.…”
Section: Introductionmentioning
confidence: 99%